Crisis management, surveillance, and digital ethics in the COVID‐19 era. (7th February 2022) - Boersma, Kees; Büscher, Monika; Fonio, Chiara
Abstract: In this special issue, we reflect on the global coronavirus disease 2019 (COVID‐19) crisis and the containment measures put in place by formal authorities, combining both theoretically and empirically three different fields of study: crisis management, surveillance studies, and digital ethics. The special issue shows how the intersection of these fields provides a great opportunity to better understand challenges that are of critical importance to today's societies, as well as opening up new avenues for innovation. The focus of this special issue is to unpack and understand the debate on crisis management measures, surveillance, and ethical consequences during the ongoing, enduring COVID‐19 crisis. Building on crisis management literature, surveillance studies, and digital ethics research the articles included in this special issue reflect on issues of governance, space, as well as moral and ethical considerations, which were often overlooked in the public discourse in relation to the COVID‐19 pandemic. The special issue provides a deeper and clearer understanding of intended and unintended ethical and political consequences of crisis management practices, such as a politics of visibility that makes the operation of power invisible and fails to combat inequality, whilst ignoring the potential positive power of digital data and surveillance for empowerment and resilience